Influence of High Temperatures on the Workability of Fresh Ready-Mixed Concrete - Victor Sampebulu (Institute for Research and Community Services, Institut Teknologi Bandung, 2012)
Properties of fresh concrete made in tropical countries, which is mixed, transported (with agitation), placed and initially cured in places where the temperature ranges from about 20oC to 40oC and relative humidity above 60%, are not completely understood. Applicable requirements also differ from country to country and government agencies and private enterprises have their own specifications. Assuming such temperature and relative humidity conditions, the present study is an attempt at evaluating the properties of hot weather concrete in fresh state with using a method of ready